2018
DOI: 10.7554/elife.39636
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functionally distinct fibro-inflammatory and adipogenic stromal subpopulations in visceral adipose tissue of adult mice

Abstract: White adipose tissue (WAT) remodeling is dictated by coordinated interactions between adipocytes and resident stromal-vascular cells; however, the functional heterogeneity of adipose stromal cells has remained unresolved. We combined single-cell RNA-sequencing and FACS to identify and isolate functionally distinct subpopulations of PDGFRβ+ stromal cells within visceral WAT of adult mice. LY6C- CD9- PDGFRβ+ cells represent highly adipogenic visceral adipocyte precursor cells (‘APCs’), whereas LY6C+ PDGFRβ+ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
346
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(378 citation statements)
references
References 53 publications
29
346
2
1
Order By: Relevance
“…WAT inflammation is associated with activation of immune cells, the presence of enlarged, unhealthy adipocytes and the accumulation of collagen fibers in the tissue. A recent study identified a new inflammatory subpopulation of cells in the adipose tissue of mice . A combined technique of single‐cell RNA‐sequencing and FACS isolation was utilized to identify the so called fibro‐inflammatory progenitors (FIPs) cells residing around the blood vessels in the visceral adipose tissue of mice .…”
Section: Adipose Tissue Resident Mϕs In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…WAT inflammation is associated with activation of immune cells, the presence of enlarged, unhealthy adipocytes and the accumulation of collagen fibers in the tissue. A recent study identified a new inflammatory subpopulation of cells in the adipose tissue of mice . A combined technique of single‐cell RNA‐sequencing and FACS isolation was utilized to identify the so called fibro‐inflammatory progenitors (FIPs) cells residing around the blood vessels in the visceral adipose tissue of mice .…”
Section: Adipose Tissue Resident Mϕs In Obesitymentioning
confidence: 99%
“…A recent study identified a new inflammatory subpopulation of cells in the adipose tissue of mice . A combined technique of single‐cell RNA‐sequencing and FACS isolation was utilized to identify the so called fibro‐inflammatory progenitors (FIPs) cells residing around the blood vessels in the visceral adipose tissue of mice . FIPs can activate immune cells in WAT and contribute to WAT remodeling and fibrosis …”
Section: Adipose Tissue Resident Mϕs In Obesitymentioning
confidence: 99%
“…This result generalized across multiple datasets of diverse biological systems, including 3,314 human lung cells (Braga et al, 2019) ( Fig. 2A), 1,378 mouse white adipose tissue stromal cells (Hepler et al, 2018) (Fig. 2B), and 1,755 human splenic nature killer cells spanning four subtypes (Fig.…”
Section: Spherical Latent Variables Help Resolve Cell Crowdingmentioning
confidence: 67%
“…Unhealthy fat tissue contains enlarged fat cells, which may die from stress. The stress this places on the surrounding tissue activates the immune system, causing inflammation and the build‐up of collagen fibers around the cells (a condition known as fibrosis) . We are inspired by the fact that in 2 weeks after treatment we observed no inflammation signs in the animal skin and in the dermis.…”
Section: Discussionmentioning
confidence: 99%